Pengaruh Pemberian Silase Pakan Komplit Berbasis Sorgum-Clitoria Ternatea dengan Konsentrat Mengandung ZnSO4 dan ZnCU Isoleusinat pada Level Berbeda Terhadap Fermentasi Rumen Kambing Kacang - Tanggela, Friscalia I.; Jelantik, I Gusti N.; Kleden, Markus M.; Lestari, Gusti A.Y (Animal Agricultura, 2024)
The study was to examine the effect of feeding silage of complete feed based on sorghum- Clitoria ternatea with increasing level of concentrates containing ZnSO4 and ZnCu isoleucineate on the rumen fermentation of kacang goats. This study used a block randomized design with 4 treatments and 3 replications. The treatments were T0=Ss-ct without concentrate, T1=Ss-ct concentrate 10%, T2= Ss-ct concentrate 20%, T3= Ss-ct concentrate 30%. The concentrate and contains 150 mg ZnSO4/kg BK concentrate and 2 % ZnCu isoleucineate/kg BK rations. The parameters measured were pH value, ammonia concentration (NH3), and total volatile fatty acid (VFA). The results showed that an increase in the proportion of concentrates containing ZnSO4 and ZnCU isoleucineate in complete feed silage based on sorghum-clitoria ternatea had no significant effect (P>0.05) on pH value, but it had a very significant effect (P<0.01) on NH3 concentration and total VFA. Based on the results of this study, it can be concluded that the complete feeding based on sorghum-clitoria ternatea silage with concentrates containing ZnSo4 and ZnCu isoleucineate does not affect the pH value but has increaes the total NH3 and VFA concentrations. A concentrate level of 20% is the best level of the concentrate supplementation.